Bullous Fixed Drug Eruption Induced by Paracetamol: Report of a Pediatric Case - Massimiliano Nino; Maria Grazia Francia; Claudia Costa; Massimiliano Scalvenzi (Karger Publishers, 2009)
Drug eruptions are among the most common adverse drug reactions, affecting approximately 3% of hospitalized patients. A fixed drug eruption (FDE) is a distinct drug-induced reaction pattern that characteristically recurs at the same skin or mucosal site. We report a case of a 2-year-old girl with bullous FDE due to Tachipirina syrup, a preparation containing paracetamol, a commonly used nonsteroidal anti-inflammatory drug in Italy.